Relation of left atrial function with exercise capacity and muscle endurance in patients with heart failure. (14th October 2021) - Bekfani, T; Ijuin, S.H; Hamadanchi, A; Bekhite, M; Nisser, J; Derlien, S; Westphal, J; Bogoviku, J; Morris, D.A; Fudim, M; Braun-Dullaeus, R.C; Moebius-Winkler, S; et al.
Abstract: Aims: Left atrial strain (LAS) and skeletal muscle endurance demonstrate a linear relationship to peak VO2. Less is known about the relationship between central (cardiac) and peripheral (muscle endurance) limitations of exercise capacity in patients with heart failure (HF). We investigated this relationship using novel cardiac markers such as LAS and left atrial ejection fraction (LAEF). Methods: We analysed echocardiographic measurements, cardiopulmonary exercise testing, and isokinetic muscle function in 55 subjects with HF and controls (17 heart failure with preserved ejection fraction -HFpEF, 18 heart failure with reduced ejection fraction-HFrEF and 20 healthy controls). Results: Patients with reduced LAEF showed reduced peak VO2: 14.3±3.5 vs. 18.5±3.5 ml/min/kg, p=0.003 and reduced muscle endurance (RME): 64.3±23.9 vs. 88.5±32.3 Nm/kg, p=0.028. Patients with reduced LAS showed similar results. Neither left ventricular global longitudinal strain (LVGLS) nor left atrial volume index (LAVI) were associated with RME. The area under the curve of LAS and LAEF in patients with HF in association with RME were (0.76 vs. 0.80) with 95% confidence interval (CI) (0.59–0.96, p=0.012 vs. 0.63–0.98, p=0.006, respectively). Peak torque of the left leg was associated with E/LAS (E: early diastolic) in patients with HFpEF (r=−0.6, p=0.020). Endurance of the left leg was associated with LAEF (r=0.79, p=0.001) in patients with HFrEF. Conclusion: LAS/LAEF are potential cardiac markers in demonstrating the link between cardiac and peripheral limitations of exercise capacity. Thus, integrating LAS/LAEF in the evaluation of exercise intolerance in patients with HF could be useful. Funding Acknowledgement: Type of funding sources: None.